2022
DOI: 10.1155/2022/3228594
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inoculation of Trichoderma asperellum with Bacillus subtilis to Promote Growth and Nutrient Absorption in Marandu Grass

Abstract: The authors have investigated the effects of different doses of mineral fertilizers combined with co-inoculation of Bacillus subtilis and Trichoderma asperellum to promote plant growth and use efficient nutrients in a plant Urochloa (Syn. Brachiaria) brizantha cv. Marandu. Individual experiments with doses of the nutrients nitrogen (N), phosphorus (P), and potassium (K) were carried out. The experiment was conducted in a completely randomized design, factorial 3 × 5. With the treatments: control noninoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…A study investigating the combined effects of chemical fertilizer doses and co-inoculated microorganisms on promoting growth and nutrient efficiency in Marandu grass demonstrated that inoculation with microorganisms, along with 50% of the recommended phosphorus dose, resulted in increased grass growth [37], which is consistent with the findings of the present study. This approach could offer a valuable solution to address the issue of low productivity and profitability in Brazilian livestock systems that are often associated with inadequate pasture management practices [11].…”
Section: Yield and Morphological Characteristics Of Marandu Grasssupporting
confidence: 91%
“…A study investigating the combined effects of chemical fertilizer doses and co-inoculated microorganisms on promoting growth and nutrient efficiency in Marandu grass demonstrated that inoculation with microorganisms, along with 50% of the recommended phosphorus dose, resulted in increased grass growth [37], which is consistent with the findings of the present study. This approach could offer a valuable solution to address the issue of low productivity and profitability in Brazilian livestock systems that are often associated with inadequate pasture management practices [11].…”
Section: Yield and Morphological Characteristics Of Marandu Grasssupporting
confidence: 91%
“…This was evident from wet and dry biomass analysis compared to control sample (Supplementary Table 1). Further, the cocultivation of T. harzianum and B. velezensis improved the mineral fertilizer availability in Urochloa brizantha leading to increased plant growth has also been reported (Costa et al 2022). Additionally, the combination of these two organisms can improve nutrient availability, stimulate phytohormone production, and carbohydrate levels in tomatoes (Zhou et al 2021).…”
Section: Discussionmentioning
confidence: 90%
“…So far, there is a lack of well-documented interaction between T22 and rhizobia in scientific literature. However, it is known that Trichoderma can enhance the activities of beneficial bacteria such as Pseudomonas or Bacillus, which contribute to improved plant health and nutrient uptake (Poveda et al 2022;da Costa et al 2022). Trichoderma species are known to produce a variety of metabolites that can play a role in shaping the composition and dynamics of soil or rhizosphere bacterial communities, influencing overall ecosystem health and plant-microbe interactions (Gao et al 2023).…”
Section: T22 Restores Nodule Bacterial Dynamics In Pea Exposed To Fe ...mentioning
confidence: 99%